2023
DOI: 10.32615/ps.2022.046
|View full text |Cite
|
Sign up to set email alerts
|

Different light-quality colored films affect growth, photosynthesis, chloroplast ultrastructure, and triterpene acid accumulation in Glechoma longituba plants

Abstract: Abbreviations: AQE -apparent quantum efficiency; BF -blue film; Car -carotenoid; Chl -chlorophyll; D -fraction of light absorbed in PSII antennae that is dissipated thermally; DM -dry mass; ETR -electron transfer rate; Ex -fraction of light absorbed in PSII antennae that is neither utilized in photosynthetic electron transport nor dissipated thermally; F0 -minimal fluorescence yield of the dark-adapted state; F0' -minimal fluorescence yield of the light-adapted state; FM -fresh mass; Fm -maximal fluorescence y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Carbohydrates are the main metabolites of primary metabolism, and their synthesis is affected by the photosynthesis rate 34 . Thus, the production of terpenoids in plants is directly linked to photosynthesis and, consequently, the biosynthesis of related precursor metabolites 35 . Zhang et al 35 demonstrated that the increase in the photosynthetic capacity of Glechoma longituba leaves under the influence of blue and green lights enhanced TTAs accumulation in this plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates are the main metabolites of primary metabolism, and their synthesis is affected by the photosynthesis rate 34 . Thus, the production of terpenoids in plants is directly linked to photosynthesis and, consequently, the biosynthesis of related precursor metabolites 35 . Zhang et al 35 demonstrated that the increase in the photosynthetic capacity of Glechoma longituba leaves under the influence of blue and green lights enhanced TTAs accumulation in this plant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the production of terpenoids in plants is directly linked to photosynthesis and, consequently, the biosynthesis of related precursor metabolites 35 . Zhang et al 35 demonstrated that the increase in the photosynthetic capacity of Glechoma longituba leaves under the influence of blue and green lights enhanced TTAs accumulation in this plant. Also, other studies indicated the crucial role of carbohydrates as precursor metabolites in the biosynthesis of plant terpenoid compounds.…”
Section: Discussionmentioning
confidence: 99%